Effect of pH on Escherichia coli Removal by Electrocoagulation and Elimination Kinetics after Treatment - A. C. Ndjomgoue-Yossa; C. P. Nanseu-Njiki; E. Ngameni (Journal of Chemistry)
There are different techniques for removing microorganisms in wastewater, each with its own advantages and disadvantages. Electrocoagulation because of its simplicity has gained great attention and is used for the removal of various ions, organic matters, and microorganisms. In this study, the effectiveness and mechanism of Escherichia coli (E. coli) removal by electrocoagulation process using aluminum and ordinary steel electrodes at different initial-pH and the kinetics of elimination of E. coli in solution after treatment were investigated. Artificial wastewater contaminated by E. coli culture was used in the experiments. The results show that the initial-pH influences significantly the effectiveness of E. coli removal. Under the experimental conditions used, more than 5 log removal of E. coli is obtained, irrespective of the nature of the electrode (ordinary steel or aluminum) and the value of the initial pH. On the one hand, the best rates of elimination are obtained for solutions that are slightly acidic (pH 5.5) and for an alkaline pH (8.5 and 10). On the other hand, the elimination decreases for a neutral solution and for a very acidic solution (pH 2.9) because of the strong resistance developed by E. coli at those pH values. For optimal treatment, the choice of electrode material depends on the initial pH. Furthermore, the study of the kinetics of elimination of E. coli after treatment shows the remanent power of the electrocoagulation process. It allows reducing treatment time and energy consumption, thus reducing the cost of treatment.